2016
DOI: 10.1074/jbc.m116.728592
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Mechanism by Which Gain-of-function Mutations to the α1 Glycine Receptor Cause Hyperekplexia

Abstract: Hyperekplexia is a rare human neuromotor disorder caused by mutations that impair the efficacy of glycinergic inhibitory neurotransmission. Loss-of-function mutations in the GLRA1 or GLRB genes, which encode the α1 and β glycine receptor (GlyR) subunits, are the major cause. Paradoxically, gain-of-function GLRA1 mutations also cause hyperekplexia, although the mechanism is unknown. Here we identify two new gain-of-function mutations (I43F and W170S) and characterize these along with known gain-of-function muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…We aimed to increase the speed reduction effect by overexpressing gain-of-function mutations in glycine receptors. The mutations are modelled on available human patient data, and correspond to zebrafish GlyRa1 I67F [18,19], GlyRa1 V304M [18,20,21], and rat GlyRa3 P185L [22]. In contrast to expectations, all of these mutations led to a moderate THN speed increase in phase 2 (approx.…”
Section: Resultsmentioning
confidence: 99%
“…We aimed to increase the speed reduction effect by overexpressing gain-of-function mutations in glycine receptors. The mutations are modelled on available human patient data, and correspond to zebrafish GlyRa1 I67F [18,19], GlyRa1 V304M [18,20,21], and rat GlyRa3 P185L [22]. In contrast to expectations, all of these mutations led to a moderate THN speed increase in phase 2 (approx.…”
Section: Resultsmentioning
confidence: 99%
“…To date, the only proposed explanation is that enhanced spontaneous GlyR activity due to gain‐of‐function mutation during nervous system development prevents formation of glycinergic synapses and thus induces shortage of inhibitory signalling in adult brain (Zhang et al . ). This, however, is unlikely the case for CGCs in cerebellar vermis, which are deprived of glycinergic synapses under healthy conditions.…”
Section: Discussionmentioning
confidence: 97%
“…) via the ablation of α1β glycinergic synapses (Zhang et al . ). This is, however, unlikely the case for the cerebellar effects associated with CGCs due to the absence (or extreme scarcity) of glycinergic synaptic connections at these cells.…”
Section: Introductionmentioning
confidence: 97%
“…Recessive hyperekplexia mutations generally result in the loss of α1 or β GlyR protein expression at the cell surface, whereas dominant mutations usually allow strong surface expression but impair channel function via reduced open probability, single channel conductance or glycine sensitivity . In addition, several GLRA1 gain-of-function hyperekplexia mutations have been detected to evoke spontaneous channel activity, which is paradoxical in that these mutations generated different levels of prolonged postsynaptic glycinergic currents but full hyperekplexia phenotype (Zhang et al, 2016). All genetic forms of hyperekplexia are successfully treated with the benzodiazepine or clonazepam Thomas et al, 2013), which acts by enhancing GABAergic synaptic transmission.…”
Section: Hyperekplexiamentioning
confidence: 99%
“…b GlyR also exhibits spontaneous activation (Zhang et al, 2016) and suggested that, like other gain-of-function startle disease mutations, W170S may cause startle disease via a developmental defect that prevents the maturation of a1b GlyR synapses (Zhang et al, 2016).…”
Section: W170smentioning
confidence: 99%